PROGRAM COMPLEX FOR MODELING OF THE DETAILS HARDENING PROCESS - S. P. Kundas; B. A. Tonconogov; Ja. S. Levashkevich; A. V. Lemzikov; I. A. Gishkeluk; P. S. Garchenko; I. S. Gauhshtein (Литьë и металлургия)
In the article there is presented the program complex ThermoSim, consisting of preprocessor, processor and postprocessor and intended for modeling (analysis) of thermalphysic processes and characteristics of details of instrument-making and machine-building, diagnostics and optimization of technological processes of heat treatment and details constructions without using the destructive control methods.